Pediatric Cancer Survivors - Wonders, Karen; Stout, Brittany (IntechOpen, 2017)
Pediatric cancer develops in 1 to 500 children. Typically, the type of cancers that develop in children is different than those that develop in adults, in that they are often the result of a DNA mutation rather than environmental or lifestyle risk factors. Leukemia, brain and central nervous system tumors, and neuroblastomas are the most common cancer types in child populations. Children tend to respond better to anticancer treatments, including chemotherapy and radiation. However, long-term side effects are common in children, often requiring follow-up care and lifestyle intervention for the rest of their lives. The percentage of 5-year survivors was over 50% for the most common cancers. This suggests that a majority of cancers in this population are highly survivable. As such, research should focus on aspects of survivorship for these individuals. This book will explore issues related to pediatric cancer and their associated treatments.